2011
DOI: 10.1210/jc.2010-2952
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Ultrasound-Guided Percutaneous Ethanol Injection Treatment in Patients with a Limited Number of Metastatic Cervical Lymph Nodes from Papillary Thyroid Carcinoma

Abstract: US-guided PEI treatment of metastatic lymph nodes seems to be an excellent alternative to surgery in patients with a limited number of neck metastases from PTC. This procedure should replace "berry picking" surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
85
0
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(91 citation statements)
references
References 22 publications
4
85
0
2
Order By: Relevance
“…There is an obvious likelihood of treating some but not all affected nodules/nodes, and we lack data on whether quality of life and prognosis are improved compared with observation or standard therapy. With these shortcomings, remarkably favorable results have been obtained using PEIT as well as ILP in patients with LN metastases from papillary thyroid cancer [74,75,76]. In 63 patients, 101 of 109 metastatic LNs responded (92 completely) to PEIT, without any significant side effects [75].…”
Section: New Methods For Preoperative Localization Of Cervical Recurrmentioning
confidence: 99%
See 1 more Smart Citation
“…There is an obvious likelihood of treating some but not all affected nodules/nodes, and we lack data on whether quality of life and prognosis are improved compared with observation or standard therapy. With these shortcomings, remarkably favorable results have been obtained using PEIT as well as ILP in patients with LN metastases from papillary thyroid cancer [74,75,76]. In 63 patients, 101 of 109 metastatic LNs responded (92 completely) to PEIT, without any significant side effects [75].…”
Section: New Methods For Preoperative Localization Of Cervical Recurrmentioning
confidence: 99%
“…With these shortcomings, remarkably favorable results have been obtained using PEIT as well as ILP in patients with LN metastases from papillary thyroid cancer [74,75,76]. In 63 patients, 101 of 109 metastatic LNs responded (92 completely) to PEIT, without any significant side effects [75]. In a feasibility study, in 5 patients with papillary thyroid cancer (8 LNs), ILP has been suggested as an alternative and to perform similarly [76].…”
Section: New Methods For Preoperative Localization Of Cervical Recurrmentioning
confidence: 99%
“…Regarding less invasive alternatives, recent publications demonstrated that percutaneous ethanol injection produced favorable results for control of recurrent thyroid cancers (10)(11)(12)(13)(14)(15).…”
Section: Methodsmentioning
confidence: 99%
“…In the last two decades, there have been reports of the development of several nonsurgical, image-guided, minimally invasive approaches for the treatment of recurrent thyroid cancer. Percutaneous ethanol injection therapy (91)(92)(93)(94), radiofrequency ablation, and laser ablation have each been reported as effective for locoregional control of cancer or for improving tumor-related symptoms in selected patients (94)(95)(96)(97)(98)(99). However, these techniques are not without complications and morbidity.…”
Section: Techniquementioning
confidence: 99%